A straightforward and sustainable synthesis of 1,4-disubstituted 1,2,3-triazoles: Via visible-light-promoted copper-catalyzed azide-alkyne cycloaddition (CuAAC) - Castro Godoy, Willber David (2017)
A simple and green synthesis of 1,4-disubstituted 1,2,3-triazoles through the effective reduction of copper(ii) assisted by organic dyes and promoted by visible light was developed. This reaction was performed under very mild conditions, using water as solvent, under a non-inert atmosphere, with low catalyst precursor loading, and in the absence of any additive. Copper and solvent recycling was successfully achieved at least three times without loss of efficiency. In addition, a safer one-step one-pot procedure was designed with very good yield.